Coronavirus disease 2019 infection and cerebrovascular diseases: an update on the pathophysiology and management. Issue 2 (22nd April 2023) - May, Brandon; Wang, David Z.
Abstract : Purpose of review: COVID-19 is an ongoing global pandemic since it was first discovered in 2020. Cerebral vascular disease and stroke are among the most common and devastating neurological manifestations of COVID-19. This review offers an up-to-date information on the possible underlying mechanism of COVID-19-related stroke, its diagnosis, and management. Recent findings: The thromboembolism associated with COVID-19 infection is likely related to the cytokine storm with innate immune activation, pulmonary disease leading to hypoxia-induced ischemia, thrombotic microangiopathy, endothelial damage and multifactorial activation of the coagulation cascade. Currently, there is no clear guidelines on the use of antithrombotics for the prevention and treatment of this phenomenon. Summary: COVID-19 infection can directly cause a stroke or facilitate the formation of thromboembolism in the presence of other medical conditions. Physicians treating patients with COVID-19 should stay vigilant about the signs and symptoms of stroke, detect and treat early.